Sustained Remission in Cannabis-Induced Psychosis treated as Schizophrenia (Journal of Psychiatrists' Association of Nepal, 2024)
Cannabis-induced psychosis and schizophrenia can present with similar symptoms making difficulties in diagnosis and treatment. We, herein, present a case of 34-year-old male with history of long term use of cannabis. He initially presented with symptoms suggestive of schizophrenia and was treated with antipsychotics. Patient would go in remission but whenever he is exposed to cannabis, would develop psychotic symptoms similar to symptoms of schizophrenia. After getting admitted in the institute, patient received comprehensive treatment focusing on cannabis abstinence and psycho-education. Over six months, antipsychotic and antidepressant medications were gradually tapered and discontinued. Following cannabis abstinence, the patient exhibited resolution of psychotic symptoms, with sustained remission, improved social engagement, and occupational stability. This case underscores the importance of cannabis abstinence in managing cannabis-induced psychosis overlapping with schizophrenia and demonstrates the potential for recovery without antipsychotic medication when substance use is effectively addressed.